EFL Teachers’ Beliefs of Classroom Seating Arrangements - Widya Dwi Septiorini; Mansyur Srisudarso; Sidik Indra Nugraha (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
The purpose of this study is to determine the seating arrangement of teachers and the reasons for their seating preferences. This study was carried out at SMK Negeri 8 Bekasi, with three English teachers serving as research subjects. This study's instruments were observations and interviews. According to the study's findings, the seating arrangement that supports students demonstrates things like comfort, flexibility in carrying out activities, completing assignments, spaciousness, and cooperation with teachers. As a result, students are supported in terms of concentration, participation in class discussions, and collaboration with teachers in order to improve student performance.